Complete genome sequence of bacteriophage Byron23 targeting Microbacterium foliorum - Moro, Francisco J. (2025)
In this paper, we report the discovery and characterization of Byron23, a bacteriophage isolated from a soil sample collected approximately 30 cm beneath the surface of a stream bank in Rosario, Santa Fe, Argentina. Byron23 infected the host Microbacterium foliorum NRRL B-24224 resulting in clear, round plaques surrounded by a turbid edge. Transmission electron microscopy revealed that Byron23 exhibits siphoviral morphology. Genome sequencing using the Illumina platform revealed a 41,821 bp genome encoding 64 predicted genes. The bacteriophage was classified within the subcluster EA1 and is predicted to be a lytic phage.